Testicular alterations in cryptorchid/orchiopexic rats chronically exposed to acrylamide or di-butyl-phthalate - Lima, Thania R. R. [UNESP]; Souza, Nathália P. [UNESP]; Cardoso, Ana P. Ferragut [UNESP]; Gomide, Lígia M. M. [UNESP]; Pontes, Merielen G. Nascimento E. [UNESP]; Miot, Hélio A. [UNESP]; Arnold, Lora L.; Cohen, Samuel M.; De Camargo, João Lauro V. [UNESP] (Japanese Society of Toxicologic Pathology, 2022)
Exposure of Sprague-Dawley (SD) rats to acrylamide (AA) or di-butyl-phthalate (DBP) from the 12th gestational day to the 16th postnatal week (PNW) has been shown to reduce the effectiveness of orchiopexy in recovering the testicular alterations associated with experimental cryptorchidism established at weaning. Herein, we provide information about the long-term effects of AA or DBP on the testes of cryptorchid/orchiopexic rats. Male offspring exposed in utero to 10 mg/kg/day AA or 500 mg/kg/day DBP underwent bilateral surgical cryptorchidism at the 3rd PNW and orchiopexy at the 6th week, with continuous exposure to the chemicals through diet until the 58th week. Regardless of the test chemical, there were severe qualitative/quantitative alterations in the seminiferous tubules and increased numbers of Leydig cells. There was an increase and decrease in the number of tubules with c-Kit- and placental alkaline phosphatase-labeled germ cells, respectively, as compared to those in the control group, suggesting an imbalance between apoptosis and cell proliferation processes. The histological scores of the testicular lesions at the end of this one-year study were higher than those in the previous 16-week study, indicating that exposure of rats to the toxicants AA or DBP enhanced the testicular alterations induced by the chemicals beginning at the intra-uterine life, and impaired the effectiveness of orchiopexy in restoring the testes to normal morphology. Although the present experimental protocol does not completely replicate the natural human undescended testes, our findings may contribute to understanding the alterations occurring in cryptorchid/orchiopexic testes potentially exposed to exogenous chemicals for extended periods.
Keywords: Acrylamide; Chronic toxicity; Di-butyl-phthalate; Orchiopexy; Rat surgical cryptorchidism; Testicular germ cells